Peran Dinas Kesehatan Dalam Pemberian Izin Pangan Industri Rumah Tangga Pada UMKM di Kelurahan Srimenanti Kecamatan Sungailiat Kabupaten Bangka - Hidayat, Wahyu; Fenyta, Fenyta; Zakiyah, Ummi (Jurnal Ilmu Administrasi Negara, 2024)
Licensing is a form of legality for both products and businesses themselves to ensure food safety and the ability to market the products safely and widely. This study aims to determine the role of the Health Department in granting Home Industry Food Permit for MSMEs in Srimenanti Village, Sungailiat Subdistrict, Bangka Regency. The research method used is qualitative research with a descriptive design. The data used are primary and secondary data. Data analysis techniques involve drawing conclusions based on observation, interviews, and document analysis. The research results show that the role of the Health Department in granting home industry food permits in Srimenanti Village, as a regulator, refers to the legal basis for granting the Household Food Industry Production Certificate (PIRT). The government's role as a facilitator provides a platform for MSMEs to conduct educational activities related to PIRT permits. The government also acts as a dynamizer by implementing capacity building through guidance and direction. It can be concluded that the role played by the Health Department has been carried out well in accordance with the provisions and objectives, although its implementation has not been fully optimized in terms of socializing it to Srimenanti Village. Recommendations for the Health Department include improving public awareness and education for MSMEs regarding PIRT permits, as well as enhancing human resources related to capacity building